Development and Pilot Evaluation of a Novel Dignity-Conserving End-of-Life (EoL) Care Model for Nursing Homes in Chinese Societies - Ho, Andy H. Y. (2017)
Purpose of the Study: The provision of end-of-life (EoL) care in long-term-care settings remains largely underdeveloped in most Chinese societies, and nursing home residents often fail to obtain good care as they approach death. This paper systematically describes the development and implementation mechanisms of a novel Dignity-Conserving EoL Care model that has been successfully adopted by three nursing homes in Hong Kong and presents preliminary evidence of its effectiveness on enhancing dignity and quality of life (QoL) of terminally ill residents. Design and Methods: Nine terminally ill nursing home residents completed the McGill Quality of Life Questionnaire and the Nursing Facilities Quality of Life Questionnaire at baseline and 6 months post-EoL program enrollment. Wilcoxon signed rank test was used to detect significance changes in each QoL domains across time. Results: Although significant deterioration was recorded for physical QoL, significant improvement was observed for social QoL. Moreover, a clear trend toward significant improvements was identified for the QoL domains of individuality and relationships. Implications: A holistic and compassionate caring environment, together with the core principles of family-centered care, interagency and interdisciplinary teamwork, as well as cultural-specific psycho-socio-spiritual support, are all essential elements for optimizing QoL and promoting death with dignity for nursing home residents facing morality. This study provides a useful framework to facilitate the future development of EoL care in long-term-care settings in the Chinese context.